Regional Practice Variation and Outcomes in the Standard Versus Accelerated Initiation of Renal Replacement Therapy in Acute Kidney Injury (STARRT-AKI) Trial: A Post Hoc Secondary Analysis - Suvi T. Vaara, MD, PhD; Ary Serpa Neto, MD, PhD; Rinaldo Bellomo, MD, PhD; Neill K. J. Adhikari, MDCM, MSc; Didier Dreyfuss, MD, PhD; Martin Gallagher, MD, PhD; Stephane Gaudry, MD, PhD; Eric Hoste, MD, PhD; Michael Joannidis, MD; Ville Pettilä, MD, PhD; Amanda Y. Wang, MD, PhD; Kianoush Kashani, MD, PhD; et al. (Critical Care Explorations, 2024)
OBJECTIVES:. Among patients with severe acute kidney injury (AKI) admitted to the ICU in high-income countries, regional practice variations for fluid balance (FB) management, timing, and choice of renal replacement therapy (RRT) modality may be significant. DESIGN:. Secondary post hoc analysis of the STandard vs. Accelerated initiation of Renal Replacement Therapy in Acute Kidney Injury (STARRT-AKI) trial (ClinicalTrials.gov number NCT02568722). SETTING:. One hundred-fifty-three ICUs in 13 countries. PATIENTS:. Altogether 2693 critically ill patients with AKI, of whom 994 were North American, 1143 European, and 556 from Australia and New Zealand (ANZ). INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. Total mean FB to a maximum of 14 days was +7199 mL in North America, +5641 mL in Europe, and +2211 mL in ANZ (p < 0.001). The median time to RRT initiation among patients allocated to the standard strategy was longest in Europe compared with North America and ANZ (p < 0.001; p < 0.001). Continuous RRT was the initial RRT modality in 60.8% of patients in North America and 56.8% of patients in Europe, compared with 96.4% of patients in ANZ (p < 0.001). After adjustment for predefined baseline characteristics, compared with North American and European patients, those in ANZ were more likely to survive to ICU (p < 0.001) and hospital discharge (p < 0.001) and to 90 days (for ANZ vs. Europe: risk difference [RD], –11.3%; 95% CI, –17.7% to –4.8%; p < 0.001 and for ANZ vs. North America: RD, –10.3%; 95% CI, –17.5% to –3.1%; p = 0.007). CONCLUSIONS:. Among STARRT-AKI trial centers, significant regional practice variation exists regarding FB, timing of initiation of RRT, and initial use of continuous RRT. After adjustment, such practice variation was associated with lower ICU and hospital stay and 90-day mortality among ANZ patients compared with other regions.